2022
DOI: 10.1093/mnras/stac1467
|View full text |Cite
|
Sign up to set email alerts
|

Scaling relations of convective granulation noise across the HR diagram from 3D stellar atmosphere models

Abstract: High-precision photometric data from space missions have improved our understanding of stellar granulation. These observations have shown with precision the stochastic brightness fluctuations of stars across the HR diagram, allowing us to better understand how stellar surface convection reacts to a change in stellar parameters. These fluctuations need to be understood and quantified in order to improve the detection and characterization of exoplanets. In this work, we provide new scaling relations of two chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…Through photometric observations, the properties of granulation as a function of stellar parameters have been revealed: CoRoT observations have shown that the granulation timescale and amplitudes decrease with the increasing characteristic frequency of the acoustic modes, the so-called frequency at maximum power ν max , which depends on the stellar surface gravity and temperature (Michel et al 2008). In line with model predictions (see e.g., Svensson & Ludwig 2005;Ludwig 2006;Trampedach et al 2013;Tremblay et al 2013;Beeck et al 2013;Samadi et al 2013;Beeck et al 2015), numerous studies based on Kepler observations (Mathur et al 2011;Bastien et al 2013;Kallinger et al 2014;Bastien et al 2016;Pande et al 2018;Bugnet et al 2018;Tayar et al 2019;Sulis et al 2020a;Rodríguez Díaz et al 2022) have also shown that the Article number, page 1 of 30 arXiv:2211.14398v1 [astro-ph.SR] 25 Nov 2022 granulation properties are dependent on the stellar fundamental parameters (T eff , logg, and [Fe/H]). Granule size increases with lower stellar surface gravities and/or larger effective temperatures, and therefore with a decreasing ν max .…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Through photometric observations, the properties of granulation as a function of stellar parameters have been revealed: CoRoT observations have shown that the granulation timescale and amplitudes decrease with the increasing characteristic frequency of the acoustic modes, the so-called frequency at maximum power ν max , which depends on the stellar surface gravity and temperature (Michel et al 2008). In line with model predictions (see e.g., Svensson & Ludwig 2005;Ludwig 2006;Trampedach et al 2013;Tremblay et al 2013;Beeck et al 2013;Samadi et al 2013;Beeck et al 2015), numerous studies based on Kepler observations (Mathur et al 2011;Bastien et al 2013;Kallinger et al 2014;Bastien et al 2016;Pande et al 2018;Bugnet et al 2018;Tayar et al 2019;Sulis et al 2020a;Rodríguez Díaz et al 2022) have also shown that the Article number, page 1 of 30 arXiv:2211.14398v1 [astro-ph.SR] 25 Nov 2022 granulation properties are dependent on the stellar fundamental parameters (T eff , logg, and [Fe/H]). Granule size increases with lower stellar surface gravities and/or larger effective temperatures, and therefore with a decreasing ν max .…”
Section: Introductionsupporting
confidence: 60%
“…16 The logg for the Kepler targets was obtained by different techniques, from the highest priority to the lowest ones, depending on availability: asteroseismology, high-resolution spectroscopy, low-resolution spectroscopy, flicker, photometric observations, and finally the KIC (see https://exoplanetarchive.ipac.caltech.edu/docs/KSCI-19097-004.pdf). able agreement with bolometric light variations of KEPLER targets (Rodríguez Díaz et al 2022). Previous studies have also used these kind of models to study the granulation signal (see e.g., Ludwig 2006;Trampedach et al 2013;Tremblay et al 2013;Samadi et al 2013), and compared their results with observations.…”
Section: Predictions From 3d Hydrodynamic Models Of Convectionmentioning
confidence: 59%
See 2 more Smart Citations
“…8 of Kallinger et al 2014). Finally, 3D hydrodynamical models of stellar granulation predict an RMS of 45.2 ppm for 55 Cnc A (see Table 2 of Rodríguez Díaz et al 2022). To compare this value with our dataset, we binned the occultation time series into 3-minute intervals and filtered the periods > 27 min (see details in Sulis et al 2022).…”
Section: Stellar Originmentioning
confidence: 91%